Perspectives on the Importance of Valorisation of Health Education Knowledge in the Student's Everyday Life - Buruleanu, Claudia Lavinia; Anghel, Gabriela Alina; Dogan, Zuhal Yilmaz (FUTURE ACAD, 2016)
The health of each people requires, first of all, the existence of an optimum nutritional status, which result from the balance between the need and the intake in terms of energy and nutrients. This status promotes the growth and the development of the body, maintains the health, enables the progress of the daily activity and participates at the body protection against different diseases. The adolescence is one of the most challenging periods of the human development, age border when perfects the shaping of the future adult. Among the characteristics of this period can be mentioned: increasing of the need in nutrients, due to the development and the faster growth in height; changes in eating habits and lifestyle; additional needs in particular situations, such as eating disorders. The research aims to analyze the perception of the students related to the importance of healthy eating habits in their daily life. To this end, it conducted a qualitative research during the workshops with Romanian and Turkish students organized in the frame of EduForHealth Project. The research objectives were: (a) measuring the level of students' satisfaction related to their knowledge concerning their healthy habits - OS1; (b) measuring the levels of importance on applying their knowledge in their daily life - OS2. The research methodology was based on the questioning technique. The measurement was done using a Likert-type scale, and the reporting and interpretation of the results was made through the Nice & Gaps method. (C) 2016 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Health education; healthy habits; satisfaction; importance; EduForHealth project; Social Sciences - Other Topics